Застосування системного підходу за умови аналізу підвищення кваліфікаційного рівня персоналу підприємства - Гармаш, Сергій Володимирович; Бойченко, Олег Ігорович (НТУ "ХПІ", 2016)
Останнім часом набули широкого розповсюдження концепції управління, які базуються на системному підході до управління організацією як системою – комплексом взаємодіючих між собою підсистем, формуючих цілісність відносно зовнішнього середовища. Сучасне промислове підприємство – це складна соціотехнічна система, то ефективна взаємодія її підсистем залежить від важливого елементу – персоналу, а саме – від рівня його розвитку.

Recently certain management concepts became widespread all over the world. These concepts are based on systems approach for management of organization as a system – a set of interactive with each other subsystems, which form integrity concerning external environment. A modern industrial enterprise is a sophisticated socio and technical system, an effective coordination of its subsystems depends on an important element – personnel, namely – the level of its professional progress. It’s especially important for Ukraine at present, when passing changes are accompanied with different vector directions of reforming processes and the reality of these reforming processes depends on our ability and willing to follow them.
Using of systems approach for analysis in rising of professional level of enterprise staff
Keywords: системний підхід; соціотехнічна система; підсистеми управління; професійний розвиток; персонал підприємства; systems approach; socio and technical system; subsystems of management; professional progress; personnel of an enterprise